The Effects of Injury on the Neuromotor Control of the Shoulder - Simpson, Hannah (East Carolina University)
Abstract: The shoulder is one of the most mobile and unstable joints in the body. When the function of the shoulder muscles is altered, and it is without the appropriate neuromotor control, the shoulder can become dysfunctional. It is unknown how previously injured individuals vary in movement patterns or whether their brains change compared to their healthy counterparts. The purpose of this study was to compare neuromotor control of the shoulder between individuals with and without a previous shoulder injury. To achieve this, we used an upper extremity task with motion capture to analyze kinematic performance of the shoulder complex and electroencephalography (EEG) to evaluate neural connectivity of the brain. We hypothesized that individuals with previous injury to the shoulder would have different kinematic patterns as well as a less direct or evasive way of achieving their goal-oriented trajectory. We also hypothesized that participants with previous shoulder injury to have more diffuse patterns of brain connectivity during performance of the task, as compared to healthy participants. Our kinematic results made it evident that healthy and post-injured individuals have different anterior/posterior trunk displacement and hand pathways toward their targets. Our neurological results showed significant changes in brain connectivity in post-injured individuals across conditions. RPE scoring increased and decreased in response to an increase and decrease in weight resistance, but scores were higher in post-injured individuals. Further research is needed to understand how individuals modify movement kinematics in different joints and determine how consistent these changes are across tasks and patterns of brain activation.
Keywords: Shoulder--Wounds and injuries; Neuromuscular diseases; Kinematics